Genomic and Virulence Characteristics of Brucella intermedia Isolated from Hospital Wastewater in Ghana - Runa Furuya; Satomi Takei; Yoko Tabe; Anthony Ablordey; Ryoichi Saito (Pathogens)
Brucella intermedia, a gram-negative, non-lactose-fermenting, aerobic, rod-shaped bacterium, is found in environmental sources (e.g., soil and water). In 2020, Ochrobactrum was reclassified as Brucella. We conducted a genomic analysis of B. intermedia from hospital wastewater samples in western Ghana. A hybrid genome assembly was constructed integrating short-read data from DNA Nanoball sequencing with long-read sequences generated by Oxford Nanopore MinION technology. Identification and antimicrobial susceptibility profiles were determined using MicroScan autoSCAN-4 based on Clinical and Laboratory Standard Institute documents. ResFinder and CARD Resistance Gene Identifier (RGI) were used to identify antimicrobial resistance (AMR) genes, and BLAST and VFDB datasets were used to identify virulence factor genes. The complete genome had two chromosomes, no plasmid, and a high average nucleotide identity value (98.05%) with B. intermedia. Resistance to trimethoprim-sulfamethoxazole was revealed, the first report in this species. CARD RGI revealed the presence of AMR genes, including ANT(9)-Ic and adeF. Local BLAST analysis revealed Cgs, a B. melitensis virulence factor. B. intermedia is an opportunistic human pathogen clinically isolated several times, suggesting the importance of accurately identifying multidrug resistance. B. intermedia may possess virulence factors similar to those of B. melitensis. Further study is needed to fully elucidate its pathogenesis.